2022
DOI: 10.3390/vaccines10050689
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines: Fear of Side Effects among German Health Care Workers

Abstract: (1) Background: Health care workers (HCWs) play a key role in increasing anti-COVID vaccination rates. Fear of potential side effects is one of the main reasons for vaccine hesitancy. We investigated which side effects are of concern to HCWs and how these are associated with vaccine hesitancy. (2) Methods: Data were collected in an online survey in February 2021 among HCWs from across Germany with 4500 included participants. Free-text comments on previously experienced vaccination side effects, and fear of sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…On online communication platforms, people tend to spread the side effects of vaccines more often than the positive effects of vaccines ( 65 ). Concerns about the side effects are a barrier to achieving high vaccination rates ( 66 , 67 ), and the perceived risk of vaccines reduces the willingness of people to receive COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…On online communication platforms, people tend to spread the side effects of vaccines more often than the positive effects of vaccines ( 65 ). Concerns about the side effects are a barrier to achieving high vaccination rates ( 66 , 67 ), and the perceived risk of vaccines reduces the willingness of people to receive COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reasons for not being vaccinated, the most common causes stated by patients included the relatively limited data on long-term consequences and the fear of thrombosis. Indeed, fear of complications is a well-known factor associated with reduced willingness for vaccination against COVID-19, even among healthcare workers [ 36 , 37 , 38 ]. Thus, appropriate educational actions are needed to propagate the benefits of COVID-19 vaccination against possible risks and increase the confidence of public to healthcare providers and vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Poland revealed that the most common reasons behind a patient’s refusal to vaccinate were: concerns about side effects; mistrust in the vaccine; and the belief that COVID-19 will not affect them [ 14 ]. Meanwhile, a study in Germany found that health care workers were most concerned about the following long- and short-term side effects of the vaccine: reactions; allergic reactions; impact on daily life; immune response; neurological side effects; and currently unknown long-term consequences on health [ 15 ]. Our study results show that family and internal medicine physicians were most exhausted by chaotic vaccination priorities and unsatisfied patients during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%